Application of nanotechnology for detection and decontamination of organophosphorus pesticides and warfare agents - Nigam, Preeti (Nanotrends, 2010)

Aptamer functionalized multifunctional fluorescent nanotheranostic platform for pancreatic cancer - Nigam, Preeti; Waghmode, Shobha A.; Yeware, Amar M.; Nawale, Laxman U.; Dagde, Priyanka; Dudhane, Amol; Sarkar, Dhiman (Journal of Nanopharm Drug Delivery, 2014)
This study explores the potential of aptamer functionalized and fluorescent silver nanoparticles (AgNPs) labeled human serum albumin nanoparticles for drug delivery and bioimaging. Nanotechnology is certainly the most promising research arena in recent years and different fields of biotechnology, medicine and agricultural have been deeply benefited by the enormous advantages of nanotechnology. In recent years, synthesis of nanoparticles via eco-friendly methods has attained a lot of interest and silver nanoparticles are synthesized extensively due to their size tunable properties and vast applicability in different areas. In this study we have explored green synthesized fluorescent silver nanoparticles as a novel bioimaging agent for pancreatic cancer. Capsaicin, a plant phytochemical found in red chilli pepper was encapsulated in aptamer MUC-1 coupled albumin nanoparticles and it was observed that the nanoformulation significantly enhanced the bioavailability and sustained release property of the drug to pancreatic cancer cells in-vitro. Meanwhile AgNPs mediated excellent bioimaging has enhanced the efficacy of our system as drug delivery vehicle.